Cosmetic Disfigurement due to Home Remedy in Melanocytic Nevi - Riya Kaur Kalra; Phulwinder Singh (Bengal Journal of Otolaryngology and Head Neck Surgery, 2018)
Melanocytic nevi of the head and neck region are common among all ages with no predilection for males or females. These moles can appear as small, dark brown spots on the skin anywhere on the face including the eyelids, which may not be cosmetically acceptable.